The critical current of disordered superconductors near 0 K - A. Doron (Nature Portfolio, 2020)
Increasing the critical current of superconductors has been a central scientific effort, but the fundamental understanding of critical currents near 0 K is lacking. Here, Doron et al. report that in disordered superconductors the critical current near 0 K is well explained by a thermal bi-stability where electrons thermally decouple from phonons in a discontinuous manner.